Tragicomedia de Calixto y Melibea - Rojas, Fernando de 1465-1541; Riquer, Martín de (Madrid 1975, 1975)
The Tragicomedy of Calisto and Melibea (Spanish: Tragicomedia de Calisto y Melibea), known in Spain as La Celestina, is a work entirely in dialogue published in 1499. It is attributed to Fernando de Rojas, a descendant of converted Jews, who practiced law and, later in life, served as an alderman of Talavera de la Reina, an important commercial center near Toledo.The book is considered to be one of the greatest works of all Spanish literature. La Celestina is usually regarded as marking the end of the medieval period and the beginning of the Renaissance in Spanish literature. Although usually regarded as a novel, it is written as a continuous series of dialogues and can be taken as a play, having been staged as such and filmedThe story tells of a bachelor, Calisto, who uses the old procuress and bawd Celestina to start an affair with Melibea, an unmarried girl kept in seclusion by her parents. Though the two use the rhetoric of courtly love, sex — not marriage — is their aim. When he dies in an accident, she commits suicide. The name Celestina has become synonymous with "procuress" in Spanish, especially an older woman used to further an illicit affair, and is a literary archetype of this character, the masculine counterpart being Pandarus.
Premiered in Burgos, 1499; first published in Salamanca, 1500
Keywords: 15th Century (1401-1500); Play (theater); Novel; Spain